JURIDICAL ANALYSIS OF FORCE MAJURE TERMINATION OF EMPLOYMENT RELATIONS IN THE JOB CREATION LAW - Suaris Firdaus Sembiring, Suaris Firdaus; Wijayati, Ani; Panjaitan, Hulman (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
The state has the responsibility to protect and promote labour in Indonesia, which is a human right in accordance with the constitution. Article 27 Paragraph (2) of the 1945 Constitution states that every citizen has the right to work and a decent life. However, labour problems continue to increase, caused by the lack of employment, the large number of workers, the low quality of workers‘ education, and the lack of supervision of workers’ rights, which reduces people's welfare. Laws in Indonesia, such as Law No. 13/2003 on Manpower and Law No. 11/2020 on Job Creation, aim to provide legal certainty and prevent arbitrary actions by employers. The regulation of labour relations is based on a work agreement that confirms the rights and obligations of all parties. Therefore, this study finds out the legal arrangements for Termination of Employment (PHK) before and after the existence of the Job Creation Law. In addition, this research also aims to analyse the legal protection of workers affected by layoffs, especially due to Force Majeur conditions after the existence of the Job Creation Law. This research uses a normative approach with qualitative juridical analysis. The data used is primary data as well as supporting data to assess the legal aspects related to termination of employment in the context of labour law in Indonesia.The new law, Job Creation, has caused controversy and dissent in the community. Previously, the layoff process required a determination from a dispute settlement institution, but with the Job Creation Law, companies can conduct layoffs with notice to workers. Legal protection for workers affected by layoffs, especially due to force majeure conditions, is important. Industrial Relations Court judges do not require a criminal court verdict for employers who conduct layoffs due to urgent offences. There are differences between Law Number 13 Year 2003 and Law Number 11 Year 2020 on Job Creation, especially in the mechanism of layoffs due to urgent violations, which are considered to violate the principle of presumption of innocence. Therefore, legal protection for workers needs to be adjusted to the principle of presumption of innocence.